Investigating factors influencing overweight and obesity among adult households in Ethiopia: a multilevel ordered analysis of 2016 EDHS data - Deressa, Alemayehu; Firdisa, Dawit; Birhanu, Abdi; Debella, Adera; Gamachu, Mulugeta; Eyeberu, Addis; Dechasa, Deribe Bekele; Jibro, Usmael; Balis, Bikila; Tolera, Moti; Regassa, Lemma Demissie; Mussa, Ibsa (Frontiers in Endocrinology, 2024)
Background: In both high-and low-income countries, including Ethiopia, overweight and obesity have emerged as concerns of public health issues of the twenty-first century. Hence, obtaining conclusive evidence concerning the factors that influence adults' body mass index is quietly important. Therefore, using representative data, our study sought to provide solid evidence on factors influencing overweight and obesity among adults in Ethiopia.The 2016 Ethiopia Demographic and Health Survey (EDHS), a dataset comprised of a nationally representative sample of the survey, served as the basis for the study. Both descriptive and analytic findings were produced using STATA version 14. The data collection was conducted from January to June 2016. A total sample of 39,749 adults, 18 years and older, were included.Predictors were assessed using multivariable ordinal logistic regression analysis, and the results were presented as an adjusted proportional ratio (POR) with a 95% confidence interval. Statistical significance was declared at a p-value of <0.05.Overall, the magnitude of overweight and obesity among adults in Ethiopia was 8.5% (95% CI = 8.2% to 8.7%) and 2.9% (95% CI = 2.7% to 3.1%), respectively. Predictor variables such as smoking (POR=0.